Pencak Silat As a Character Building Strategy for Madrasah Ibtidaiyah Negeri 2 Serang Students; Thomas Lickona's Perspective - Anggita Citra, Ririn; Khaeroni, Khaeroni; Farhurohman, Oman (AT-THULLAB : Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
Juvenile delinquency is currently rampant in society. There are many cases such as brawls, acts of violence, and truancy at school; for this reason, character formation in children is very important to be implemented from an early age. The study aims to analyze the strategy of instilling character values through extracurricular pencak silat at MIN 2 Serang, an Islamic elementary school in Serang, Banten. MIN 2 Serang was chosen as the location of the study because it has shown a positive impact on the formation of student character through pencak silat activities, which are part of the local culture of Banten. This study uses a qualitative approach with a descriptive case study method, and this study found that instilling character values is carried out through three stages: moral knowing, feeling, and doing. The results of the study indicate that the Character Value Instillation Strategy instilled by the trainer, namely using the Moral Knowing Strategy, fosters discipline, Moral Feeling instills empathy, and Moral Doing instills the value of responsibility, but from this instillation, there are supporting factors, including adequate facilities. At the same time, challenges such as the distance of students' homes become obstacles to character formation. This study contributes to developing a character education model rooted in local culture.